Monster hands - Kane, Karen, 1965-; McMillan, Jonaz (Nancy Paulsen Books, 2024)
"One night, just before bedtime... Milo read a book about a monster under the bed. Milo should not have read that book. Monsters under the bed are scary, but luckily, Milo's best friend, Mel, knows just what to do--scare the monster more than the monster scares you!"--Page [2] of jacket.